The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/03075079.2016.1266612
|View full text |Cite
|
Sign up to set email alerts
|

Learning facilitating leadership

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 65 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Being a student leader may provide useful social ties to high-ability students, which can strengthen and expand their social networks in the school-to-work transition phase (Baert and Verhaest, 2018;Kramarz and Skans, 2014). This is in parallel with the contemporary understanding of leadership, which emphasises creating social capital and leaders building relations with their environments (Fiedler, 1996;Rasmussen and Hansen, 2018), rather than the idea of leadership based on personal qualities that restrict leadership with individuals and their abilities. In this sense, student leaders come into contact with highlevel decision-makers as well as peers inside and outside the university to help them find higher paying jobs to match with their qualities more quickly (Kramarz and Skans, 2014;Li et al, 2010;Lundin et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Being a student leader may provide useful social ties to high-ability students, which can strengthen and expand their social networks in the school-to-work transition phase (Baert and Verhaest, 2018;Kramarz and Skans, 2014). This is in parallel with the contemporary understanding of leadership, which emphasises creating social capital and leaders building relations with their environments (Fiedler, 1996;Rasmussen and Hansen, 2018), rather than the idea of leadership based on personal qualities that restrict leadership with individuals and their abilities. In this sense, student leaders come into contact with highlevel decision-makers as well as peers inside and outside the university to help them find higher paying jobs to match with their qualities more quickly (Kramarz and Skans, 2014;Li et al, 2010;Lundin et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Researchers believe that leadership concepts and practices can be taught to most individuals to enhance their leadership effectiveness (Doh, 2003). Rasmussen and Hansen (2016) further highlighted the importance of acquiring skills and competencies that allow academics to develop as leaders as well as researchers. Surveys by the UK's Leadership Foundation for Higher Education (LFHE) (2015; 2016) found that over 90% of traditional HE institutions supported their staff in delivering leadership development to over 3,400 individuals.…”
Section: Approaches For Academic Leadership Developmentmentioning
confidence: 99%